Implementación de la evaluación para el aprendizaje en un curso de Ingeniería durante la emergencia sanitaria de la COVID-19 - Franco, Rosendo (2022)
The traditional evaluation approach (based on practices and exams) domains at engineering courses. In 2020 and 2021, the COVID-19 pandemic forced the adaptation of teaching materials and methodology of these courses; however, the form of evaluation remained practically the same. In the Mechanics for Engineers (MI) course, the course evaluation was online but consisted of four (4) qualified practices and two (2) common (synchronous) exams. In 2022, within the framework of an educational innovation project, it was decided to implement an evaluation for learning strategy in this course. It was defined that formative evaluation would have 50% of the total course grade and that summative evaluation (that is, the exams) would have the remaining 50%. Also, it was determined that formative activities would repeat on a weekly basis. This article presents the design of the evaluation strategy, the development of the necessary resources for it, the implementation experience and the students' perceptions about it.